Pengaruh Keterampilan, Disiplin Kerja, Dan Kepuasan Kerja Terhadap Produktivitas Kerja Karyawan - Sri Wahyu Lelly Hana Setyanti; Sudarsih Sudarsih; Dela Audiva (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The increasingly fierce competition in the business world has an impact on the business sector that continues to develop and innovate. In this case, it is necessary to have good human resource management because the activities carried out in a company are measured by the productivity of the employees involved in completing the work. This study aims to analyze the effect of skills, work discipline, and job satisfaction on employee productivity. The population of this study were all employees of Rumah Batik TatsakaBanyuwangi, totaling 32 employees. The research data used primary data and secondary data. Methods of data analysis using multiple linear regression analysis method. Hypothesis testing was carried out using a t-test which basically showed the partially significant effect of the independent variables on the dependent variable. The results obtained indicate that the variables of skills, work discipline, and job satisfaction have a positive and significant influence on employee work productivity.